An unusual presentation of a metastatic adenocarcinoma of the cervix with a rectovaginal fistula arising from a primary sigmoid adenocarcinoma in the postpartum period - case report - Harjit S Dhaliwal; Rachana Dwivedi; Tharanga Gunasekera; Jasmina Glogic (Barpeta Obstetrics and Gynaecological Society, 2021)
Colorectal cancer in pregnancy and in the postpartum period is rare. We report a case of a 38-year-old woman with metastatic adenocarcinoma of the cervix in the postpartum period. Due to the rarity and lack of insight of this condition, she visited various clinicians and was finally referred to secondary care based on feculent material seen vaginally and also palpation of an abdominal mass in the left iliac fossa. Cervical biopsy confirmed a colorectal primary and CT and MRI, which showed a locally advanced tumor invading the posterior cervical and anterior rectal wall. MRI suggested T4N2. Given the locally advanced stage, the patient was counseled by the colorectal surgeons the need for neoadjuvant therapy with chemo or radiotherapy prior to embarking on surgery with the possibility of adjuvant therapy thereafter. Colorectal cancer in pregnancy and the postpartum period is associated with challenges being clinical, diagnostic and therapeutic which often leads to a delayed diagnosis in the advanced stage, which invariably carries a poor prognosis.